1981
DOI: 10.1136/bmj.282.6271.1197
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin treatment in Friedreich's ataxia.

Abstract: haemolysis (which may affect the rate). Serum is fibrinogen-free, and it is simple to measure the viscosity of plasma and serum separately. We investigated the value of paired plasma viscosity and serum viscosity measurements in predicting the development of chronic rheumatic disease in a population with acute symptoms attending a special early-arthritis clinic. Patients, methods, and resultsWe investigated 115 consecutive patients attending a clinic specifically for patients with early rheumatic complaints. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…31 The GABA transaminase inhibitor, gamma-vinyl GABA, has no effect in OPCA and FA patients, 32 and lecithin, a precursor of acetylcholine, is not beneficial in FA. 33 Dopaminergic mechanisms probably play a role. HVA levels are low in both FA an OPCA patients, and AH is known to release dopamine from neurons.…”
Section: Discussionmentioning
confidence: 99%
“…31 The GABA transaminase inhibitor, gamma-vinyl GABA, has no effect in OPCA and FA patients, 32 and lecithin, a precursor of acetylcholine, is not beneficial in FA. 33 Dopaminergic mechanisms probably play a role. HVA levels are low in both FA an OPCA patients, and AH is known to release dopamine from neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Their in vivo responses have been evaluated previously. [22][23][24][25] For each surfactant, the foam samples were divided into five experimental groups and one control group. The other apparatuses used in this study included a cylinder of CO 2 gas, medical gloves, medical three-way valves, 5-mL syringes, a black backplane, a camera, and a set of stents.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication, Livingstone et al, (1981) reported some functional improvement in upper limb coordination in three of seven patients with Friedreich's Ataxia, four of six patients with primary cerebellar degeneration and three of seven patients with mixed ataxia, after twelve weeks of oral choline chloride supplements. More recently, Pentland et al, (1981) failed to demonstrate any significant difference in upper limb functions (timed handwriting, spiral drawing and rapid repetitive finger movements) in twelve patients with Friedreich's Ataxia supplemented with pure lecithin during the first and the third month of a threemonth period.…”
Section: Introductionmentioning
confidence: 98%